2011
DOI: 10.1021/nl203332e
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous Graphene as a Lithium–Air Battery Electrode

Abstract: The lithium-air battery is one of the most promising technologies among various electrochemical energy storage systems. We demonstrate that a novel air electrode consisting of an unusual hierarchical arrangement of functionalized graphene sheets (with no catalyst) delivers an exceptionally high capacity of 15000 mAh/g in lithium-O(2) batteries which is the highest value ever reported in this field. This excellent performance is attributed to the unique bimodal porous structure of the electrode which consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
759
3
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 960 publications
(787 citation statements)
references
References 44 publications
16
759
3
9
Order By: Relevance
“…The uniform distribution of nanosized Li2O2 intimately contacting with highly conductive CNTs facilitate the smooth decomposition across large interface area at lower charge potential and thus the Li2O2 could be sufficiently decomposed after charging (Fig. 4d) [2, 30,61,63]. After 10 th discharge, the structure of Fe@NCNT is well preserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniform distribution of nanosized Li2O2 intimately contacting with highly conductive CNTs facilitate the smooth decomposition across large interface area at lower charge potential and thus the Li2O2 could be sufficiently decomposed after charging (Fig. 4d) [2, 30,61,63]. After 10 th discharge, the structure of Fe@NCNT is well preserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, great efforts have been devoted to developing the cathode catalyst with high activity and stability for oxygen-involved reactions in Li-O2 batteries [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Peng et al [7] firstly reported the rechargeable Li-O2 batteries by catalyzing the reversible formation/decomposition of the Li2O2 on porous Au catalyst, which makes Li-O2 batteries promising for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] This porous 1D structure will be even more promising for increasing the catalytic activities toward the two key processes in lithium oxygen battery, oxygen reduction reaction (ORR) (O 2 + 2Li + + 2e − → Li 2 O 2 ) and the oxygen evolution reaction (OER) (Li 2 O 2 → O 2 + 2Li + + 2e − ) by facilitating rapid O 2 diffusion and electrolyte accessibility, and providing more catalytic reaction sites for deposition of Li 2 O 2 . [15][16][17][18][19][20] More importantly, this 1D nanostructured catalyst may solve many of the inherent catalytic problems associated with stateof-the-art nanoparticulate catalysts. [21][22][23] The porous NTs are characterized by their uniquely anisotropic nature, which offers advantageous structural and electronic factors to the catalytic reduction of oxygen.…”
Section: Doi: 101002/adma201502262mentioning
confidence: 99%
“…During the first discharge process, the Ni‐NG composites gradually become thickened and high‐density particles densely aggregate on the large space between Ni‐NG (Figure 4a,b). Particularly, different from the fully dense structure of the cathodes after the discharge process for some Li‐O 2 and Li‐CO 2 batteries,7, 8, 9, 26, 27, 28 Ni‐NG still maintains the porous structure with wrinkled nanosheets 29, 30, 31. In addition, it is obvious that the discharged products are composed of thin films and agglomerate particles around Ni granules with much more porous and thinner structure than individual graphene,7 and Ni‐NG could efficiently contribute to the homogeneous distribution of discharge products.…”
mentioning
confidence: 95%